(untitled) (FUDMA JOURNAL OF SCIENCES, 2020)
The study was carried out to evaluate the functional properties of fresh and powdered egg albumin and yolk. The experiment was carried out at Animal Product and Processing lab of the Department of Animal Science, Federal University Dutsinma. Fresh eggs were collect from the Departmental farm. Ten (10eggs) each were weighed and crushed into stainless dish and separated into albumin and yolk for sun drying. After 8 hours of sun drying the crystals were convert into powder form using grinding and sieving techniques. Samples of the powder albumen and yolk were then subjected to functional properties determination. Data collected were analyzed using Statistical Analysis System (SAS) version…2002. The result indicates that there is significant (P<0.05) differences in functional properties of both fresh and powdered Albumin. Egg white (Albumin) fresh had Foaming capacity and Foaming stability values of 20.00% and 9.66% while egg white (Albumin) powdered Foaming capacity and Foaming stability had a lesser values of 11.00 % and 2.33% respectively. The Emulsification capacity (EC) and Emulsification Stability (ES) of Fresh Albumin seems to differ having a lower value (P<0.05) functional properties of 7.00% and 2.66%, while the Emulsification capacity (EC) and Emulsification Stability (ES) of powdered Albumin had higher value (P<0.05) of 35.66% and 4.00%. Similarly the Water Absorption Capacity (WAC) and Swelling Capacity (SC) for Fresh Albumin have a lower value (P<0.05) of 1.00% and 2.00%, while the Water Absorption Capacity (WAC) and Swelling Capacity (SC) of powdered Albumin had higher